2018
DOI: 10.5152/eurasianjmed.2018.170320
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nausea and Vomiting on Anxiety and Depression Levels in Early Pregnancy

Abstract: Objective: Nausea and vomiting of pregnancy (NVP) have been reported to be associated with distinct physiological responses to psychosocial stress. In this study, we aimed to evaluate the impact of nausea and vomiting on anxiety and depression during pregnancy.Materials and Methods: Eighty-three pregnant women with nausea and vomiting and 83 healthy pregnant women were included. All participants completed the demography-and pregnancy-related questionnaire, including Rhodes Index of Nausea and Vomiting, Beck An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 23 publications
3
27
0
Order By: Relevance
“…On the other hand Beyazit and Sahin found that according to Beck Anxiety Inventory (BAI) severe anxiety is higher in hyperemesis gravidarum cases than in controls (61.1% vs10.8%) respectively with no statistical significance [21].…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand Beyazit and Sahin found that according to Beck Anxiety Inventory (BAI) severe anxiety is higher in hyperemesis gravidarum cases than in controls (61.1% vs10.8%) respectively with no statistical significance [21].…”
Section: Discussionmentioning
confidence: 96%
“…This condition can last a long time and affects the physical, psychological and social conditions of pregnant women (Lacasse et al, 2008;Munch et al, 2011). Pregnant women can experience lack of energy, fatigue; irritability, anxiety and even become dehydrated as a result of nausea and vomiting during pregnancy (Beyazit & Sahin, 2018;Heitmann, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…As many as 13% of pregnant women experienced nausea and vomiting until 20 weeks of pregnancy (Mahmoud & Ahmed Ibrahim, 2013). Nausea and vomiting on pregnancy was found to disturb daily life functions of the pregnant women, including caring for children (84%), reduce work productivity (94%) and quality of life and also elevate anxiety level (Heitmann, 2017;Beyazit & Sahin, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, little is known about the persistent form of NVP (during the second and third trimester of pregnancy), that no progressed to HG. Beyazit and Sahin (2018) found that pregnant women with severe NVP experienced a higher level of anxiety and depression during pregnancy and Iliadis et al (2018) found that women with prolonged nausea have increased risk of depressive symptoms when their children were 2 months.…”
Section: Problem Statementmentioning
confidence: 99%
“…In recent years, particular attention has been paid to the study of possible risk factors associated with the postpartum depression (Ghaedrahmati et al, 2017;Smorti et al, 2019) and on postpartum anxiety (Dennis et al, 2016). In this field, recent studies have shown the association between some physical symptoms during pregnancy, such as nausea, vomiting, sleepiness and increased psychopathological symptoms in mothers (Beyazit & Sahin, 2018;Iliadis et al, 2018;Leeners et al, 2000).…”
Section: Introductionmentioning
confidence: 99%